Analisis Tingkat Penjuaan Kue Dengan Mekanisme Penjualan Konsiyasi di Toko Al-Khidmah Nurzaman Metro Lampung - Fellita Nur Faizah; Hendri Irawan; Laili Zakiya; Mila Santi; Nabila Maharani; Carmidah Carmidah (CiDEA Journal, 2023)
This study aims to analyze the level of cake sales with a consignment sales mechanism at Al-Khidmah Nurzaman Store in Cendrawasih Market Metro Lampung. The research used a field study method with interview data collection techniques. The results showed that the level of cake sales with the consignment system was higher than regular sales. The consignment sales rate grew 56% while regular sales were only 44%. The commission sharing system between cake owners (pengamanat) and shop owners (commissioners) is adjusted based on the agreement, which is 10-20% of the selling price per product. The consignment system is effective for both parties because the commissioner does not need additional capital and the pengamanat can expand marketing, although the pengamanat must apply specific criteria to avoid losses due to damage or unsold products.